Green Communication in Environmental Campaigns: A Study of Commercial Brand Strategies for Millennials and Gen Z - Nurjanah Nurjanah; Firayani Firayani; Olivia Tahalele (Journal of Dialogos, 2025)
This study aims to analyze the green communication strategies used by commercial brands in environmental campaigns and evaluate how Millennials and Gen Z respond to these messages. The research method uses a descriptive qualitative approach with content analysis of digital campaigns of several commercial brands and in-depth interviews with respondents from Millennials and Gen Z. The results show that green communication strategies that emphasize sustainability storytelling, transparency, and interactive participation on social media are more effective in building engagement and loyalty of young consumers. Millennials tend to value long-term brand consistency on environmental issues, while Gen Z demands more instant transparency and direct interaction. This study confirms that message authenticity is a determining factor in the success of environmental campaigns as well as strategic differentiation in building a sustainable brand image.